Students’ Perception of Listening Material in Extensive Listening - Afi Ni'amah; Ika Lusi Kristanti (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2022)
Extensive listening takes an essential role in improving students’ listening skill. Extensive listening provides or promote students’ comprehension and enjoyment in class activity or listening practices. The success of extensive listening is depended on having easy the access of right materials. The present study examines on students’ perception of listening material in extensive listening. The present study only focuses on the materials are designed for some meeting in extensive listening class. In this regard, the material is meant to provide students with L2 listening proficiency. Allowing the students exploring YouTube channel is destined to have proper and pleasure material. In order to know the suitability and inclination of the material, descriptive qualitative research is conducted. This study undertakes interview to students who have participated in extensive listening class. The research findings reveal that the students’ perception on listening material are: 1) listening material motivates and engage students in listening skill, 2) students are very enthusiasm in discussing material of their own choice, and 3) extensive listening material is appropriate for listening practices. Because the material in extensive listening can expand their knowledge about the topic that they have chosen, enhance their word recognition in speech, and explores students’ ability regarding normal speech rate.